Duplication of the Sphenomandibular Ligament - Simonds, Emily (Cureus, 2017)
The normal origin of attachment of the sphenomandibular ligament is from the spine of the sphenoid bone and derailment of its course might interfere with mandibular nerve anesthetic blockade. During routine dissection of the skull base and mandibular region, a case of an anatomical variation of the sphenomandibular ligament was observed. The ligament was found to be composed of two parts; an anterior part with a wide origin from the spine of the sphenoid bone and a posterior part arising from the mandibular fossa of the temporal bone. This case and related literature were reviewed. To our knowledge, a split sphenomandibular ligament has not been previously reported. Such a variation should be kept in mind by oral surgeons and dentists during procedures in this area such as inferior alveolar nerve anesthetic blockade